Chemical surface modification of lithium disilicate needles of a silica-based ceramic after HF-etching and ultrasonic bath cleaning: impact on the chemical bonding with silane - A Poulon-Quintin; F Rouzé l'Alzit; E Ogden; A Large; C Bertrand; M Bartala (Journal of Dental Problems and Solutions - Peertechz Publications, 2022)
Recommendations to obtain the best bonding to silica-based ceramics are to prepare its surface by hydrofluoric-acid HF etching and regular application of a silane. This study investigated how the HF-etching followed by ultrasonic water bath cleaning or by an additional phosphoric acid treatment impacts the adhesion properties of a resin (G-CEM LinkForce®) with a lithium disilicate glass-ceramic (IPS Emax Press, Ivoclar Vivadent). Comparison is based on results obtained with HF etching and direct silane application. After HF-etching, a water ultrasonic bath (4 minutes), and a final air drying, the scratch test critical load increases (+ 46%) thanks to chemical bonding. Additional tests are presented including heat treatments (at 85 °C before and after silanization). If HF-etching is followed by phosphoric acid treatment and drying of silane at 85 °C, scratch test critical load increases (+ 42%) due to mechanical bonding. Similar adhesion properties are obtained with two opposite protocols.